Radical surgery for stage IB2/IIA2 cervical cancer: A large retrospective study - Zhou, Fang; Tang, Xuedong; Shao, Zhuyan; Chen, Xi; Gao, Wen; Fang, Chenyan; Wang, Zejia; Zhang, Ping; Zhu, Tao; Tang, Huarong (Frontiers in Oncology, 2022)
Background We aimed to evaluate survival, complications, and prognostic factors in patients with IB2/IIA2 (FIGO 2009, bulky early-stage) cervical cancer (CC) who were primarily treated with radical surgery (RS). Methods From January 2011 to January 2018, patients with stage IB2/IIA2 CC who underwent RS ± adjuvant therapy were enrolled and retrospectively evaluated. Survival was estimated using the Kaplan–Meier method. Significance was determined using the log-rank test. Multivariate regression analyses were performed to determine prognostic factors. Results Of the 975 enrolled patients, 877 (89.9%) received adjuvant therapy. The median follow-up was 48 months, the 5-year overall survival (OS) was 85.9%, and the 5-year progression-free survival (PFS) rate was 80.8%. Multivariate analysis showed that histological type, pelvic lymph nodes, and para-aortic lymph nodes were independent prognostic factors for PFS and OS. Tumor diameter was also an independent prognostic factor with OS. Recurrent disease developed in 14.3% (140) of patients., including local, distant, and both recurrences in 55 (5.6%), 71 (7.3%), and 14 (1.4%) patients, respectively. Grade 3–4 short-term complications occurred in 196 (20.1%) patients, and long-term complications occurred in 86 (8.8%) patients. Short-term hematological complications occurred in 99 cases (10.2%). No significant differences in non-hematological complications were detected between the RS and RS + adjuvant therapy groups. Conclusions RS followed by adjuvant therapy is a feasible and effective treatment for IB2/IIA2 CC, with a high 5-year survival rate and an acceptable incidence of complications. Positive pelvic lymph nodes and para-aortic abdominal lymph nodes significantly impact PFS and OS. Evaluation of lymph node status before surgery is important. RS is recommended for patients with negative lymph node metastasis.